Evaluation of pulmonary ventilation in COVID-19 patients using oxygen-enhanced three-dimensional ultrashort echo time MRI: a preliminary study. Issue 5 (May 2021) - Zhao, F.; Zheng, L.; Shan, F.; Dai, Y.; Shen, J.; Yang, S.; Shi, Y.; Xue, K.; Zhang, Z.
Abstract : AIM: To evaluate the lung function of coronavirus disease 2019 (COVID-19) patients using oxygen-enhanced (OE) ultrashort echo time (UTE) MRI. MATERIALS AND METHODS: Forty-nine patients with COVID-19 were included in the study. The OE-MRI was based on a respiratory-gated three-dimensional (3D) radial UTE sequence. For each patient, the percent signal enhancement (PSE) map was calculated using the expression PSE = (S100% – S21% )/S21%, where S21% and S100% are signals acquired during room air and 100% oxygen inhalation, respectively. Agreement of lesion detectability between UTE-MRI and computed tomography (CT) was performed using the kappa test. The Mann–Whitney U- test was used to evaluate the difference in the mean PSE between mild-type COVID-19 and common-type COVID-19. Spearman's test was used to assess the relationship between lesion mean PSE and lesion size. Furthermore, the Mann–Whitney U -test was used to evaluate the difference in region of interest (ROI) mean PSE between normal pulmonary parenchyma and lesions. The Kruskal–Wallis test was applied to test the difference in the mean PSE between different lesion types. RESULTS: CT and UTE-MRI reached good agreement in lesion detectability. Ventilation measures in mild-type patients (5.3 ± 5.5%) were significantly different from those in common-type patients (3 ± 3.9%). Besides, there was no significant correlation between lesion mean PSE and lesion size. The mean PSE of COVID-19 lesions (3.2 ± 4.9%) was significantly lower than that of the pulmonary parenchyma (5.4 ± 3.9%). No significant difference was found among different lesion types. CONCLUSION: OE-UTE-MRI could serve as a promising method for the assessment of lung function or treatment management of COVID-19 patients. Highlights: CT and UTE-MRI reached good agreement in lesion detectability. Severity of COVID-19 is correlated with pulmonary ventilation. OE-UTE-MRI have potential for evaluating lung function of COVID-19 patients.